2014
DOI: 10.2215/cjn.02730313
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Outcomes, and Comparisons across Definitions of AKI in Hospitalized Individuals

Abstract: SummaryBackground and objectives At least four definitions of AKI have recently been proposed. This study sought to characterize the epidemiology of AKI according to the most recent consensus definition proposed by the Kidney Disease Improving Global Outcomes (KDIGO) Work Group, and to compare it with three other definitions.Design, setting, participants, & measurements This was a retrospective cohort study of 31,970 hospitalizations at an academic medical center in 2010. AKI was defined and staged according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
258
4
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(303 citation statements)
references
References 42 publications
18
258
4
13
Order By: Relevance
“…Our choice to consider only moderate to severe AKI (KDIGO stages 2-3) as events and lump stage 1 AKI together with no AKI is arguable. We note that although many studies have demonstrated the importance of even mild fluctuations in renal function (1,8,26), the most consistent relationships with adverse outcomes are seen with more severe disease (8,29). Indeed, some data suggest that some patients without clinical evidence for AKI may still have subclinical injury as detected by biomarkers and supported by changes in long-term outcomes including death and dialysis (30).…”
Section: Discussionmentioning
confidence: 86%
“…Our choice to consider only moderate to severe AKI (KDIGO stages 2-3) as events and lump stage 1 AKI together with no AKI is arguable. We note that although many studies have demonstrated the importance of even mild fluctuations in renal function (1,8,26), the most consistent relationships with adverse outcomes are seen with more severe disease (8,29). Indeed, some data suggest that some patients without clinical evidence for AKI may still have subclinical injury as detected by biomarkers and supported by changes in long-term outcomes including death and dialysis (30).…”
Section: Discussionmentioning
confidence: 86%
“…KDIGO identified more AKI due to the addition of the criterion of an absolute increase in creatinine of 26.5 lmol/L over 48 h to the RIFLE definition and extending the time-limit from 48 h to 7 days for percentage increase of creatinine of 50% in the AKIN definition. 16 A comparison of the performance of the three AKI classification systems in 1900 post-cardiac surgery patients showed that AKI incidence (25.9%) and staging were identical when using KDIGO and AKIN, while RIFLE identified fewest (24.9%) patients with AKI. 17 Similar findings were also reported in a study with 3100 critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Seven observational studies251, 252, 253, 254, 255, 256, 257 examining patient mortality rate as a clinical outcome were extracted during an assessment comparing the KDIGO guidelines and the AKIN and RIFLE criteria, and as a result of comparing AKI diagnoses based on the KDIGO guidelines with diagnoses based on the RIFLE or AKIN criteria, diagnoses based on the AKIN criteria were found to have higher accuracy or were reflective of similar in‐hospital mortality rates. Although only the study by Peng et al 257.…”
Section: Cq12: Acute Kidney Injury/blood Apheresismentioning
confidence: 99%